Caracterización de eventos adversos de medicamentos antirretrovirales reportados al Programa de farmacovigilancia Bogotá D. C., 2008-2016 (2017)
The human immunodeficiency virus (HIV) according to WHO, is defined as an infection that attacks the immune system of a living being that will gradually deteriorate called "immunodeficiency", this type of virus can be transmitted by maintaining relationships Vaginal, anal, or oral sex with a person infected with HIV, another factor that influences HIV transmission is contaminated blood transfusions or perhaps the sharing of needles, syringes, or other sharp instruments previously in contact with a Positive person in HIV. On the other hand, it can also be transmitted from the mother to the child during the gestation, delivery and breastfeeding process When a patient is diagnosed with HIV, it is essential that they experience an immediate change in their lifestyle, diet, physical exercise and the most appropriate pharmacological treatment. Antiretrovirals are used as chronic treatments to control viral load and improve the immune system, but studies have shown that adverse events reported to the district pharmacovigilance program are high, taking into account that combinations of medications are also used that may increase the possibility Of interactions and adverse events in the patient. In the present study, it was possible to identify certain adverse reactions typical of antiretroviral drugs, which are of vital importance when evaluating and monitoring patients who are receiving antiretroviral treatment, the statistics issued by WHO and UNAIDS on the Prevalence of HIV disease among males. On the other hand it is evidenced that the majority of adverse reactions are of Serious Non-seriousness -Moderado by what is determined that there was the need to intervene professional health without causing greater risks on treated patients. Finally, it is emphasized that it is important that pharmacovigilance and pharmaceutical care programs must be further strengthened in order to propose alternatives that allow safe and effective management of patients who present adverse reactions and thus generate optimization and / Or reducing costs in health care as well as raising awareness and stressing the importance of pharmacy as the main actor in the acquisition, storage and dispensing of medicines as well as ratify the importance of the Pharmaceutical Chemist and his knowledge of the drug which gives The ability to provide support to patients and generate an education about the rational use of medicines.